Sichtbarkeit und Medium. Austausch, Verknüpfung und Differenz naturwissenschaftlicher und ästhetischer Bildstrategien - Zimmermann, Anja (Hamburg University Press, 2005)
Knowledge formations are always also image information. Scientific processes of knowledge therefore belong to a cultural practice that encompasses both visual and knowledge traditions. The essays collected in this volume examine scientific and artistic visualizations in the transitional zones between art and science and thus combine historical and pictorial issues. The topics range from microscopy in popular science books of the 17th and 18th centuries and the debate about ghost photography in the late 19th century to visualizations of the tobacco mosaic virus in the present.